BELAJAR MEMBACA TEKS BAHASA INGGRIS DENGAN PENGENALAN PHONICS BERSAMA SD ISLAM DUTA EKSELENSIA, DEPOK - Hafizah Rifiyanti (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2021)
Reading is an activity that has many benefits. Through reading, a person will be able to gain a lot of insight and knowledge. Therefore, reading habits should be enhanced as early as possible. Learning to read is a phase that must be passed in order to read writing fluently. Learning to read is an essential foundation for becoming an educated person. Reading offers opportunities for pleasure, to increase our knowledge of the world and to enhance our imagination and creativity. In learning English, reading is an obstacle for some people, especially since how to read text in English is very different from Indonesian. This often happen to starter learners. Compared to tests in Indonesian, the spelling that must be pronounced is different from the writing in English. Since, English is one of the foreign languages ​​that must be studied in Indonesia, learning about English in addition to mastery of vocabulary that must be developed, must also be started by reading and pronouncing writing in English correctly. In several primary schools in Indonesia, both national and international, the method of learning to read written or text in English uses the Phonics method and approach. Phonics is a method for teaching the reading and writing of an alphabetic language. However, many schools do not understand what phonics is and its benefits. In connection with this, an introduction to phonics is carried out at SDI Duta Ekslesnsia, Citayam, Depok, Jawa Barat